Exploring the causes of the slowdown in remittances to Mexico. - Ruiz, I; Vargas-Silva, C (Springer Verlag, 2011)
This article explores the slowdown of remittances to Mexico and the role that may have been played by some key variables from the United States economy. The findings show that several measures of United States economic activity and different proxies for the unemployment of Mexican nationals living in the United States do not appear to have a strong impact on remittance transfers. On the other hand, this study finds that United States housing variables do seem to affect remittance transfers. In particular, there is a special prominence of the impact shown by the number of housing starts in the United States. Overall, the results seem to suggest that there is not a single United States economic factor that is responsible for the decrease of remittances to Mexico but rather a combination of factors. Among these factors, the decrease in United States housing activity seems to play a major role.